Pengaruh Viskositas Kitosan Gel Terhadap Penggunaannya di Proses Penyembuhan Luka - Sularsih Sularsih (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2013)
Chitosan powder when dissolved with acetat acid solution gives viscous solution. The accessibility of chitosan depends on viscosity of its solution. The viscosity determines the extent of penetration of chitosan. The aim of this study was to account the proliferation cells on wound healing process of dental extraction using different viscosity of chitosan gel. Rattus nornegicus strain wistar male, aged 8-16 weeks, divided into 2 treatment groups namely group 1 which given chitosan gel with high viscosity and group II which given chitosan with low viscosity. Chitosan were applied into the socket of dental extraction. Rat was decaputated 7 and 14 days after chitosan application and the jaw in the treated regions and control group were cut for histopatological to observe the proliferation cells. Data were analyzed using t test. The result showed significant differences of proliferation cells between groups with high and low viscosity of chitosan. The group with high viscosity of chitosan have more higher of proliferation cells.(p<0,05). The viscosity can influence the absorbtion of chitosan that accessibility to its application on proliferation cells of wound healing process.